PENGUATAN KOMPETENSI PEDAGOGIK GURU MELALUI STRATEGI ACTIVE LEARNING DENGAN MODEL JIGSAW DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DI MI - Munawir; Muhammad Mifta Khussurur; Annisa Darojati Illyin (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2026)
Islamic Cultural History (learning in Madrasah Ibtidaiyah generally encounters issues like low student interest due to traditional, repetitive teaching methods that rely too much on rote memorization. This study aims to investigate the importance of teacher pedagogical skills and the impact of using Active Learning strategies through the Jigsaw model on enhancing the quality of SKI learning. The research method applied is qualitative with a library research approach. Data were gathered from various primary and secondary sources such as books and relevant journal articles, then examined using qualitative descriptive techniques. The findings indicate that teacher pedagogical skills are a vital element in developing adaptive learning innovations. The use of the Jigsaw model proves effective in changing the classroom environment to be more engaging through the "Expert Group" and "Home Group" systems. This model can enhance individual accountability, self-confidence, and student retention of historical knowledge through the peer teaching method. The conclusion of this study is that the Jigsaw model Active Learning strategy is notably better than conventional lecturing methods in reviving Islamic historical values and boosting student engagement, as long as the teacher acts as a disciplined and creative facilitator.